Assessing the natural-healing behavior of adhesively bonded structures under dynamic loading. (1st October 2019) - Brandtner-Hafner, M.H.
Abstract: For adhesively bonded structures, maximizing their longevity under the aspect of minimizing costs of maintenance and repair are basically of high interest for the operator. Specifically, high-tech industries such as aeronautical, automotive or medicine are subject to very high standards in terms of quality, performance and safety. Hence, for stakeholders of such industries it is crucial to know how repeating damage cycles affect the structural integrity of a glued structure. The question which might arise is what minimum significant residual strength and fracture-healing recovery rate is needed in order to prevent a total structural collapse. To pursue such crucial issues, a novel study has been conducted for investigating the natural fracture-healing behavior of several well-established types of industrial adhesives. In doing so, an innovative test setup was utilized to identify new sophisticated damage parameters, which cannot be found in any technical data sheet of adhesive manufacturers. Thanks to both the utilization of an innovative test device and the application of the G F -concept, an independent material parameter was thereby ascertained, which is highly representative and suitable for characterizing dynamic damage behavior of real structures outside the lab. The remarkable findings revealed that only one distinct type of adhesive was suitable for showing significant fracture-healing behavior. This was empirically verified by different mechanical and fracture analytical benchmarks, such as bulk tensile strength, interface tensile strength and fracture resistance. The results obtained demonstrated the efficacy of the novel applied G F -concept for successfully evaluating both the damage tolerance and healing behavior of adhesively bonded structures. In conclusion, this examination showed that the inclusion of fracture analysis already in the adhesive selection and evaluation process is crucial for maximizing the quality, performance and safety of glued structures during lifetime operation.